Advancing mitochondrial genome data interpretation in missing persons casework. Issue 1 (December 2019) - Marshall, Charla; Sturk-Andreaggi, Kimberly; Ring, Joseph D.; Taylor, Cassandra R.; Barritt-Ross, Suzanne; Parson, Walther; McMahon, Timothy P.
Abstract: Massively parallel sequencing techniques have made possible the adoption of mitogenome sequencing for missing persons casework. In order to expand the family pedigree and population data necessary for sequence comparisons and statistical analysis, complete mitochondrial genome (mitogenome) haplotypes were generated by the Armed Forces Medical Examiner System's Armed Forces DNA Identification Laboratory using an automated laboratory workflow and robust analysis pipeline. Over 600 CEPH family pedigree samples from 87 lineages were processed in order to characterize the expected number of differences in mitogenome sequences between maternal relatives. Although stochastic artifacts in the CEPH cell lines elevated the point heteroplasmy rate three-fold compared to population sample data (1.8 vs. 0.46 point heteroplasmies per individual, on average), the CEPH family sequences exhibited a maximum of two substitutions between any two maternal relatives in nearly 500 generational events. The family study furthermore showed that elevating the variant detection threshold may create false substitutions at heteroplasmic sites. Results from an initial 2000 reference database samples indicate a first-pass success rate of 85%, with 97% unique mitogenome haplotypes. These data demonstrate advancements made toward the interpretation of mitogenome sequence data in missing persons casework.